A Socio-pragmatic Analysis of Women Expressive Utterances in Bad Moms Movie - Permatasari, Afelia Intan; , Dra. Siti Zuhriah Ariatmi, M. Hum (2017)
This research focuses on expressive utterances showed by women in Bad Moms movie. This research has two major bjectives (1) to describe the intentions of women expressive utterance, and (2) to describe the politeness strategies of women expressive utterances in Bad Moms movie. This research is qualitative research. The data in this research are utterances showed by women that support the occurrence of expressive utterances. The data source is Bad Moms anuscript by John Lucas and Scott Moore. The data are collected by using documentation and observation. The result of the research shows that (1) fifteen types of expressiveutterance intention used by women in Bad Moms movie. 13 utterances belong to praising (12%), 14 utterances belong to apology (13%), 3 utterances belong to expressing sympathy (3%), 7 utterances belong to expressing frightened (6%), 2 tterances belong to expressing hope (2%), 2 utterances belong to expressing hopeless (2%), 4 utterances belong to expressing tired (4%), 5 utterances belong to expressing gratitude (5%), 3 utterances belong to expressing proud (3%), 11 utterances belong to expressing pleasure (10%), 17 tterances belong to expressing displeasure (15%), 4 utterances belong to expressing love (4%), 5 utterances belong to expressing like (5%), 9 utterances belong to expressing dislike (8%), 9 utterances belong to expressing surprised (8%). The dominant type of the intention of expressive utterance used by women is expressing displeasure (15%). It can be concluded that angry characteristic that is dominant used by men,it is dominant too at women in this movie. Women characters in this movie based on different context and situation usually use the feeling of being upset and annoyed. (2) the researcher found four types of politeness strategies in Bad Moms movie based on Brown and Levinson's theory: 48 terances belong to bald on record strategy (45%), 22 utterancesbelong to positive politeness strategy (20%), 29 utterances belong to negative politeness strategy (27%), and 9 utterances belong to off record strategy (8%). The dominant of liteness strategy of expressive utterance used by women is bald on record strategy (45%). It can be concluded that women are not always more polite in using language than men. Women do not attempt to minimize the threat to the hearer's face because the speaker wishes to maximize the efficiency of the utterance.